2011
DOI: 10.1080/19393210.2010.539707
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ochratoxin A occurence in Greek wines

Abstract: A total of 150 wines, including 123 dry wines (64 red, 49 white and 10 rosé) and 27 dessert wines (14 red and 13 white), were obtained from various viticulture and oenological practices across Greece during the period 1999-2006 and analyzed for ochratoxin a (OTA) using immunoaffinity clean-up and HPLC with fluorescence detection. There was a high frequency of OTA in commercially available wines (69% positive samples). However, the level of contamination was relatively low, with only one sample marginally reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…Greek wines from 1999 to 2006 had 69% positive samples but with low OTA concentrations: one sample contained the EU permitted maximum level and 91% had < 1.0 μg L − 1 . The higher concentrations were in wines from the south, and in sweet wines (Labrinea, Natskoulis, Spiropoulos, Magan, & Tassou, 2011): red wines had high levels (Soufleros, Tricard, & Bouloumpasi, 2003). Very high median and mean values of 0.466 and 0.833 μg L − 1 were obtained for six table wines which were similar to values previously reported for sweet wines (Burdaspal & Legarda, 2007).…”
Section: Presence Of Ochratoxin a In Winesupporting
confidence: 85%
“…Greek wines from 1999 to 2006 had 69% positive samples but with low OTA concentrations: one sample contained the EU permitted maximum level and 91% had < 1.0 μg L − 1 . The higher concentrations were in wines from the south, and in sweet wines (Labrinea, Natskoulis, Spiropoulos, Magan, & Tassou, 2011): red wines had high levels (Soufleros, Tricard, & Bouloumpasi, 2003). Very high median and mean values of 0.466 and 0.833 μg L − 1 were obtained for six table wines which were similar to values previously reported for sweet wines (Burdaspal & Legarda, 2007).…”
Section: Presence Of Ochratoxin a In Winesupporting
confidence: 85%
“…Statistical analysis revealed that OTA levels in organic wines were not significantly different from that found in conventionally produced ones. The same results were found by Labrinea et al [52] in conventional and organic wines from Greece. Table 1 gathers the most significant reports regarding the occurrence of OTA in wine worldwide.…”
Section: Agricultural and Harvesting Practicessupporting
confidence: 80%
“…Sweet wines are frequently contaminated and they often reach high levels of OTA that sometimes exceed the legal regulations [6,49,50,52,58]. This fact could also be related to winemaking techniques, although oenological practices vary widely among the different types of sweet wine [71].…”
Section: Fate Of Ochratoxin a During Winemakingmentioning
confidence: 99%
“…Wine samples collected from northern, western, and central Greece showed 22 contaminated samples of 43 tested, whereas southern Greece and the Aegean Islands had 54 positive of 77 samples and 28 positive of 30 samples, respectively. 15 Brera et al 18 also observed a gradually increasing mean concentration from northern (0.05 ng/mL) to southern Italy (0.54 ng/mL). This may be due to the hotter and more humid conditions that can favor better the growth of the Aspergillus carbonarius and the consequent production of OTA.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%